Open Source Software. - Gaff, Brian M.; Ploussios, Gregory J. (Computer (00189162), 2012)
The sixth in a series of articles providing basic information on legal issues facing people and businesses that operate in computing-related markets focuses on open source software. The featured Web extra at http://youtu.be/8fCFrSv9cjE is an audio recording of the Computing and the Law column connected to the sixth in a series of articles providing basic information on legal issues facing people and businesses that operate in computing-related markets. In it, Computing and the Law coauthors Brian M. Gaff and Gregory J. Ploussios discuss common legal pitfalls that businesses encounter and when and why businesses should be prepared to get legal advice.